Four new species of Paraclius Loew (Diptera: Dolichopodidae) from the Brazilian Atlantic Forest, and notes on the systematic position of Cheiromyia Dyte - Capellari, Renato Soares; de Souza Amorim, Dalton (Zootaxa, 2009)
Four new species of Paraclius Loew from the Brazilian Atlantic Forest are described and illustrated: P. amphiatheratus, sp. nov., P. parenti, sp. nov., P. sagittatus, sp. nov., and P. dicrophallus, sp. nov. The condition of their enlarged sperm pump, also seen in the Neotropical genus Cheiromyia Dyte, is briefly discussed. Comments on the phylogenetic position of Cheiromyia are presented in light of new data from female terminalia of that genus.